Identification of crustacea allergens by crossed radioimmunoelectrophoresis - Lehrer, S B; McCants, M L; Salvaggio, J E (International archives of allergy and applied immunology, 1985)
Crossed immunoelectrophoresis (CIE) detected 18 precipitating antigens in extracts of shrimp. Of these antigens, crossed-line immunoelectrophoresis (CLIE) of shrimp extract demonstrated that 5 cross-reacted with crayfish, 3 with lobster and 1 with crab extract. Allergens present in the shrimp CIE plates were identified by crossed radioimmunoelectrophoresis (CRIE) using sera from 6 study subjects who were skin-test and RAST positive to shrimp extract. Of the 7 allergens detected, 3 (precipitins 1, 3 and 6) reacted with most of the 6 sera tested from shrimp-sensitive subjects. Precipitins 1 and 6 appear to be common crustacea allergens (present in shrimp, crayfish, lobster and crab) whereas precipitin 3 may be a specific allergen since it is present only in shrimp.